ROSSMIX 2.0: A Simplified Meso‐Scale Eddy Closure Applied to a Realistic Ocean Model - Carsten Eden; Jan Dettmer (Journal of Advances in Modeling Earth Systems)
Abstract A new closure, ROSSMIX 2.0, for the effect of meso‐scale eddies in non‐eddy‐resolving ocean models is presented and evaluated. It combines aspects of several previous closures in a simplified approach: local linear stability analysis is used to predict the vertical and lateral shape of eddy correlations, while a wave energy equation co‐integrated in the ocean model predicts their amplitudes. The new closure is implemented and evaluated with good success in an idealized channel model of vertical and lateral shear instability, and in a realistic quasi‐global ocean model. The new closure enhances the meridional overturning circulation both globally and in the individual basins, with clearer connection of the large‐scale overturning cells in the Southern Ocean. This comes along with enhanced northward heat transport and horizontal transports in better agreement with observations, and a reduced bias in watermasses.